The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/hsc.12460
|View full text |Cite
|
Sign up to set email alerts
|

Timing of return to work and women's breastfeeding practices in urban Malaysia: A qualitative study

Abstract: Nearly half of the working population in Malaysia are women, and with only a short period of maternity leave, they may struggle to achieve the recommended 6 months of exclusive breastfeeding. The aim of this paper was to explore the relationship between the timing of return to work and beliefs and breastfeeding practices among women in urban Malaysia. A qualitative inquiry based on a phenomenological framework and multiple methods was used: face-to-face interview, participant diary and researcher field notes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…However, despite the challenges, some did continue EBF until 6 months because of their positive attitude regarding the benefits of EBF. Similar findings are reported in a study conducted among employed women in Malaysia (Sulaiman et al, 2018). Sulaiman et al (2018) found that the time of returning to work was a hindrance to EBF for some mothers but not for others.…”
Section: Delay Returning To Work Before 6 Monthssupporting
confidence: 89%
See 1 more Smart Citation
“…However, despite the challenges, some did continue EBF until 6 months because of their positive attitude regarding the benefits of EBF. Similar findings are reported in a study conducted among employed women in Malaysia (Sulaiman et al, 2018). Sulaiman et al (2018) found that the time of returning to work was a hindrance to EBF for some mothers but not for others.…”
Section: Delay Returning To Work Before 6 Monthssupporting
confidence: 89%
“…Similar findings are reported in a study conducted among employed women in Malaysia (Sulaiman et al, 2018). Sulaiman et al (2018) found that the time of returning to work was a hindrance to EBF for some mothers but not for others. This might be because maternal behaviour is the main contributor in determining the duration of EBF.…”
Section: Delay Returning To Work Before 6 Monthssupporting
confidence: 89%
“…Given the declining frequency and duration of breastfeeding during recent decades in Malaysia, the observed lower frequency of breastfeeding in HR‐positive cases compared to HR‐negative cases is also consistent with the rising HR‐positive cancers in contrast to the falling HR‐negative cancers. However, the association of breastfeeding with cancer subtypes in our study is contradictory with results based on a systematic review summarizing 27 studies that reported a stronger protective effect of breastfeeding for HR‐negative cancers (especially for triple‐negative cancer) compared to HR‐positive cancers .…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, we considered socio-demographic information on mothers collected at recruitment, without taking into account any changes that occurred during the follow-ups at 1 and 2 years. For instance, it could be interesting to evaluate in the future whether women who return to work after maternity leave exhibit different compliance with breastfeeding recommendations [ 61 , 62 ]. Secondly, the proportion of infants who were breastfed until 2 years was low, not allowing us to determine what factors might be associated with prolonged breastfeeding with complementary feeding.…”
Section: Discussionmentioning
confidence: 99%